O Brasil com z : representações de Brasil em alguns processos enunciativos estadunidenses - Silva, Adriano Henriques Lopes da (2016)
On this dissertation, we decided to choose American discourse resources to be part of our analysis about the representations of Brazil in the USA (United States of America) in 2012 and 2013. In order to achieve our objective, we chose two different analysis resources: the speech of American ETAs (English Teacher Assistants) at the Federal University of Uberlândia in 2014 and also the news about Brazil and its different characteristics. This research considers that the economic and political aspects of a country interfere on the way the country is represented in a global scenario. In fact, the economy growth, in many cases, is what makes it possible the construction of an imaginary about a country which was barely spoken about before. Therefore, the dissertation considers the period that Brazil still supports a representation of emerging nation abroad as its discourse object, and problematizes the discursive movements which follow the image of Brazil from a third world country to an emerging economy. The theoretical approach to develop the research is the French Discourse Analysis (FDA), because we believe that the FDA field can bring about questions about politics, economy and society, derived from its theories and the discourses produced by the subjects. Hence, the FDA is not only a simply field that concerns language issues, but it is also a field of knowledge that problematizes issues about the subject and how he or she inscribes him/herself in language. The hypothesis that raised our interest in investigating the representation of Brazil came from the fact that, under the influence of journalistic discourse, the ETAs discursive memory is built by old stereotyped conceptions of Brazil and new conceptions, like the ones of a country in development. For that reason, Brazil supports an image of being in suspension. In this way, the research s interests were to find out the representation of Brazil on the ETAs speeches, as well as analyse the effects that this speeches raise about Brazil. Futhermore, it was important to research the representations on the journalistic discourses in the period it was analyzed. It was also important to understand how the discourses work within the representations and if it is possible to recognize the interdiscursivity between the representations of Brazil on the news and on the ETAs speeches. The analysis was focused on detecting the representations on the corpus, discussing its discursive operation in order to point out new possible conceptions of Brazil on the ETAs discursive memory. We aim to investigate the extent of a discursive memory of Brazil in relation to journalistic discourses about the country, understanding to what extent the discursive memory of Brazil is constituted be the journalistic discourse.